2022
DOI: 10.1002/joc.7660
|View full text |Cite
|
Sign up to set email alerts
|

A characterization of clouds over the Great Barrier Reef and the role of local forcing

Abstract: A characterization of cloud properties associated with precipitation in the region around the Great Barrier Reef (GBR) is constructed using decadelong (2007-2017) satellite observations from Moderate Resolution Imaging Spectroradiometer (MODIS) and Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observations (CALIPSO) combined with CloudSat. The spatial and vertical distributions of low-level cloud properties over the region are also investigated and discussed. In general, different cloud types are obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 80 publications
(103 reference statements)
0
0
0
Order By: Relevance
“…It is interesting to note that the orographic enhancement of the low-level cloud fraction, extending to the eastern water area, potentially provides a sheltered area for the coral reefs, protecting them from severe bleaching through reducing the solar radiation heating. This result is consistent with the observational analysis presented by Zhao et al (2022), which highlighted a notable increase in the frequency of low-level clouds associated with orographic enhancement in the Wet Tropics. Figure 9 shows the map of accumulated precipitation over the inner-most domain from 1 km WRF simulations from the CTRL-run, and the difference between CTRL-run and sensitivity studies, respectively.…”
Section: Orographic Effectssupporting
confidence: 92%
See 3 more Smart Citations
“…It is interesting to note that the orographic enhancement of the low-level cloud fraction, extending to the eastern water area, potentially provides a sheltered area for the coral reefs, protecting them from severe bleaching through reducing the solar radiation heating. This result is consistent with the observational analysis presented by Zhao et al (2022), which highlighted a notable increase in the frequency of low-level clouds associated with orographic enhancement in the Wet Tropics. Figure 9 shows the map of accumulated precipitation over the inner-most domain from 1 km WRF simulations from the CTRL-run, and the difference between CTRL-run and sensitivity studies, respectively.…”
Section: Orographic Effectssupporting
confidence: 92%
“…Bonell and Gilmour, 1980), with the Bellenden Ker Top station receiving over 8000 mm of annual precipitation (Herwitz, 1986) on average. Zhao et al (2022) found significant orographic enhancement of low-level clouds not only over the Wet Tropics, but also over the upwind ocean extending partially over the GBR. It is therefore of interest to examine any upwind effect of orographic enhancement on shallow cloud and precipitation through high-resolution numerical simulations, where interactions of local variability associated with topography and coastal processes are better resolved.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations